First Report of Turtles from the Himalayan Kingdom of Bhutan - Wangyal, Jigme Tshelthrim; Wangchuk, Dorji; Das, Indraneil (Chelonian Research Foundation, 2012)
Five turtle species, Cuora amboinensis, C. mouhotii, Cyclemys gemeli, Melanochelys tricarinata, and Indotestudo elongata, are reported for the first time from the Himalayan Kingdom of Bhutan. The record of C. mouhotii represents a significant range extension to the west; that of C. amboinensis represents a range extension across a political border from the same landscape in adjacent Northeast India; and those of C. gemeli, M. tricarinata, and I. elongata fill geographic gaps in their known distributions. An analysis of distributions of other turtle species in adjacent eastern Nepal and Northeast India suggests that additional country records of turtles may be found in Bhutan, especially in the southern lowlands of the country.